2010
DOI: 10.1029/2007rg000242
|View full text |Cite
|
Sign up to set email alerts
|

Geophysics at the interface: Response of geophysical properties to solid-fluid, fluid-fluid, and solid-solid interfaces

Abstract: [1] Laboratory studies reveal the sensitivity of measured geophysical properties to solid-fluid, fluid-fluid, and solid-solid interfaces in granular and fractured materials. In granular materials, electrical properties and nuclear magnetic resonance relaxation times exhibit a strong dependence on the size and properties of the solid-fluid interface. The electrical and seismic properties of granular materials and the seismic properties of fractured materials reveal a dependence on the size or geometry of fluid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 128 publications
(179 reference statements)
0
30
0
2
Order By: Relevance
“…In recent years there is a growing interest in using geophysical methods in general, and geoelectrical methods in particular in detecting and monitoring organic contamination in the subsurface [e.g., Vanhala et al , 1992; Borner et al , 1993; Atekwana et al , 2000; Aal et al , 2006; Kaufmann and Deceuster , 2007; Cassiani et al , 2009; Schmutz et al , 2012; Schwartz et al , 2012]. Of these methods, the spectral induced polarization (SIP) is a promising method as it is sensitive to both pore fluid content and characteristics, and to mineral‐fluid interfaces and their chemical composition [ Jougnot et al , 2010; Knight et al , 2010]. The general idea with the SIP method is to inject an alternating current through two electrodes and to measure the resultant potential between two other electrodes located along the current path.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there is a growing interest in using geophysical methods in general, and geoelectrical methods in particular in detecting and monitoring organic contamination in the subsurface [e.g., Vanhala et al , 1992; Borner et al , 1993; Atekwana et al , 2000; Aal et al , 2006; Kaufmann and Deceuster , 2007; Cassiani et al , 2009; Schmutz et al , 2012; Schwartz et al , 2012]. Of these methods, the spectral induced polarization (SIP) is a promising method as it is sensitive to both pore fluid content and characteristics, and to mineral‐fluid interfaces and their chemical composition [ Jougnot et al , 2010; Knight et al , 2010]. The general idea with the SIP method is to inject an alternating current through two electrodes and to measure the resultant potential between two other electrodes located along the current path.…”
Section: Introductionmentioning
confidence: 99%
“…The geochemical monitoring suggested that the primary mode of interaction between biochar and OMW is adsorption, a process that is expected to alter the surface properties of biochar and consequently the imaginary component of complex conductivity (Lesmes and Frye ; Knight et al . ; Kemna et al . ) (Figs and ).…”
Section: Resultsmentioning
confidence: 99%
“…; Muller et al . ). Wavelength scale flow occurs between peaks and troughs of the seismic wave; mesoscale WIFF occurs between lithological layers, inclusions and in‐homogeneities; while pore‐size scale flow occurs between adjacent pores of different compliances, such as matrix and cracks (Pride et al .…”
Section: Introductionmentioning
confidence: 97%